Compliance to national guidelines on the management of chronic obstructive pulmonary disease in Malaysia: a single experience - Mohd Shah, Azarisman Shah; Hasmoni, Mohamed Hadzri; Abdul Rani, Mohammed Fauzi; Mohd. Anshar, Fauzi; M. P. A., Faizal; Abdul Manap, Roslina; Harun, Roslan (Singapore Medical Association, 2008)
Introduction: Malaysia has a high rate of smoking prevalence and the figure is increasing. Although there has been many local and regional studies on the prevalence and symptomatology of chronic obstructive pulmonary disease patients, data is lacking on the degree of compliance to national management guidelines in the treatment of chronic obstructive pulmonary disease. Methods: 86 patients who attended the respiratory outpatient clinic of the Hospital Universiti Kebangsaan Malaysia were enrolled into a prospective, observational study. Results: 88 percent of the patients were male and the majority was ethnically Chinese (65 percent). The majority of patients were in the moderate to very severe categories, with a mean FEV1 of 0.97 +/− 0.56 L/sec and predicted mean FEV1 percentage of 43.1 +/− 21.3 percent. 58 percent of the patients were on long-acting beta-agonist, 65 percent were on inhaled steroids, and only 16 percent were on scheduled pulmonary rehabilitation. Conclusion: The low uptake rate for long-acting beta-agonist and pulmonary rehabilitation could be attributed to several factors. Financial cost, the need for strict compliance to a structured rehabilitation regime, lack of significant social support and clear up-to-date guidelines are possible reasons.